Elements of Architecture : Assembling archaeology, atmosphere and the performance of building spaces - Bille, Mikkel (Archaeological Orientations, 2016)
Cover -- Title -- Copyright -- Contents -- List of figures -- List of contributors -- Acknowledgements -- 1 Into the fog of architecture -- 2 On behalf of form: the view from archaeology and architecture -- PART 1 Form and temporality -- 3 On shaping buildings -- 4 Immanent architecture -- 5 Big affects: size, sex and Stalinist 'architectural power' in post-socialist Warsaw -- 6 Architecture in ruins: Palladio, Piranesi and Kahn -- 7 Building lives -- 8 Archaeologies of an informal city: temporal dimensions of contemporary Andean urbanism -- 9 Brussels' conflicting constructs (photo essay) -- PART 2 Atmospheres -- 10 A sense of place -- 11 Lighting up the atmosphere -- 12 Traffic architecture: hidden affections -- 13 Affective architecture in Ardnamurchan: assemblages at three scales -- 14 A sense of architecture in the past: exploring the sensory experience of architecture in archaeology -- PART 3 Performance and process -- 15 Architecture in motion -- 16 Politics of architectural imaging: four ways of assembling a city -- 17 Homeless, home-making, and archaeology: "To be at home wherever I find myself " -- 18 Into architecture: house-building and acentred personhood in Maputo, Mozambique -- 19 Sedimentation and sentiment: destabilizing architecture at the post-industrial Mexican periphery -- 20 Performance architecture: absence, place and action -- 21 Reframing the ziggurat: looking at (and from) ancient Mesopotamian temple towers -- PART 4 Disintegration and unfinishedness -- 22 Architecture becoming new spaces -- 23 Incipient ruination: materiality, destructive agencies and repair -- 24 For love of ruins -- 25 Unfinishing buildings -- 26 The disconnected experience of some designed places -- 27 Failure? An archaeology of the architecture of nuclear waste containment -- Index.